Peningkatan Mutu Abon Ikan dan Jabu Jabu Khas Desa Madello dengan Mesin Modern - Awaluddin, Sri Prilmayanti; Rasdi , Rasdi; Mubarak, Fhahri; Haijal, Ahmad; Putri, Hera Nur; Muntasir, Muntasir (Penerbit Goodwood, 2025)
Purpose: to improve the quality and production of fish floss and jabu-jabu brand